FENOMENA KHUTBAH JUMΓÇÖAT DI KOTA MANADO (Harmoni, 2012)
Friday sermons/Khutbah(s) (speeches)  have been one of the methods of religious proselytizing in the Muslim community that is always conducted in various places. The  writing is the result of research on the Friday sermons in Manado City as an area that is not predominantly Muslims. The research was conducted with a qualitative approach, and data collection techniques through interviews, document review, and observation. The results show that although the Friday sermon is a consistent proselytizing routine, the mosques which hold Friday prayers have hardly prepared the delivery of the themes. The themes of the speeches are more normative, and a few were based upon Islamic economic activity, harmony, and the establishment of tolerance. One potential implementation is a Friday sermon preacher characteristics that most have an undergrad educational background (S1), and some have post graduate degrees. Various problems faced by preachers are such as minimum financial rewards, the rare training program for the preachers, and the target coverage area is extensive with limited transportation.
Keywords: Manado dan Islam; Khotib; Khutbah JumΓÇÖat; Manado and Islam; Khatib (preacher); Friday sermon